Expression of the growth hormone secretagogue receptor 1a (GHS‐R1a) in the brain - Marat I. Airapetov; Sergei O. Eresko; Andrei A. Lebedev; Evgenii R. Bychkov; Petr D. Shabanov (Physiological Reports, 2021)
Abstract The review presents data on the expression of growth hormone secretagogue receptor 1a (GHS‐R1a) in the brain regions in model animals (zebrafish, rodents, primates), and in the human brain. Studies show widespread distribution of the receptor in the brain, which evidences the involvement of the receptor in many physiological processes. Using various organisms, data have been obtained regarding the participation of the GHS‐R1a in the regulation of the anti‐ and pro‐inflammatory response, proliferation, and apoptosis. It is known that the receptor plays an important role in eating behavior and is also involved in the pathogenetic mechanisms of drug addiction, obesity, and chronic alcohol consumption. Based on this, research is underway with the use of various therapeutic agents that can be used for the pharmacological correction of these conditions. This review also presents hypothetical pathways of intracellular signaling, in which GHS‐R1a may participate. A complete understanding of these mechanisms has not yet been reached. The ghrelin intracellular signaling seem to be specific to brain region and, probably, also depend on the metabolic or stress status of the organism.